Rocks support a distinctive and consistent mycobiome across contrasting dry regions of Earth. Issue 3 (17th March 2022) - Coleine, Claudia; Delgado-Baquerizo, Manuel; Albanese, Davide; Singh, Brajesh K; Stajich, Jason E; Selbmann, Laura; Egidi, Eleonora
Abstract: Rock-dwelling fungi play critical ecological roles in drylands, including soil formation and nutrient cycling; however, we know very little about the identity, function and environmental preferences of these important organisms, and the mere existence of a consistent rock mycobiome across diverse arid regions of the planet remains undetermined. To address this knowledge gap, we conducted a meta-analysis of rock fungi and spatially associated soil communities, surveyed across 28 unique sites spanning four major biogeographic regions (North America, Arctic, Maritime and Continental Antarctica) including contrasting climates, from cold and hot deserts to semiarid drylands. We show that rocks support a consistent and unique mycobiome that was different from that found in surrounding soils. Lichenized fungi from class Lecanoromycetes were consistently indicative of rocks across contrasting regions, together with ascomycetous representatives of black fungi in Arthoniomycetes, Dothideomycetes and Eurotiomycetes. In addition, compared with soil, rocks had a lower proportion of saprobes and plant symbiotic fungi. The main drivers structuring rock fungi distribution were spatial distance and, to a larger extent, climatic factors regulating moisture and temperature (i.e. mean annual temperature and mean annual precipitation), suggesting that these paramount and unique communities might be particularly sensitive to increases in temperature and desertification. Abstract : Rock-dwelling fungi play critical ecological roles in drylands, including soil formation and nutrient cycling; we found that the main drivers structuring their distribution were spatial distance and, to a larger extent, climatic factors regulating moisture and temperature, suggesting that these paramount and unique microorganisms might be particularly sensitive to increases in temperature and desertification.